PENGALAMAN RUANG REKREASI PESISIR SAMPUR DI KOJA SEBAGAI AKUPUNKTUR PERKOTAAN - Reynalda Samil; Sutarki Sutisna (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2022)
Urban acupuncture is a method to improve urban areas that have degraded. The decline or degradation has occurred in Koja, North Jakarta since 1994, when the Sampur Beach area and Koja Shops disappeared. Activities and attractions that occur experience degradation of movement. The memories are still attached to the residents, it can be seen from the residents who are still conveying their sadness through online platforms. Now, people's recreation areas in Koja are minimal, since Sampur coastal tourism has been abolished. The urban acupuncture method was used to restore the memory of the residents of Koja into a more relevant form, namely a recreational trip to the memory of the coast of Sampur. The writing method used is to find primary and secondary data in the literature and survey the daily activities of local residents. The daily activities of residents in the past such as bathing, bathing at the beach, socializing, sunbathing and so on, as well as current activities were adapted into programs in buildings. The proposed program then uses the narration method and spatial experience so that the memory of the narrative to be conveyed can be felt by visitors. The proposed intervention, which is a recreational trip, is expected to restore local recreation and the movement of local residents. Keywords:  urban acupuncture; memory; recreational site; narration Abstrak Akupunktur perkotaan adalah sebuah metode untuk memperbaiki kawasan kota yang memiliki degradasi. Penurunan atau degradasi terjadi di Koja, Jakarta Utara sejak tahun 1994, ketika kawasan Pantai Sampur dan Pertokoan Koja hilang. Aktivitas dan atraksi yang terjadi mengalami degradasi pergerakannya. Memori dan kenangan masih melekat pada warganya, terlihat dari warga yang masih menyampaikan kesedihannya melalui platform online. Kini, tempat rekreasi warga di Koja sangat minim, semenjak wisata pesisir Sampur ditiadakan. Metode akupunktur perkotaan digunakan untuk mengembalikan memori warga Koja ke dalam bentuk yang lebih relevan, yaitu sebuah perjalanan rekreasi memori pesisir Sampur. Metode penulisan yang digunakan adalah dengan mencari data primer dan sekunder secara literatur dan survei aktivitas keseharian warga sekitar. Kegiatan sehari-hari warga pada masa lampau seperti berendam, mandi di pantai, bersosialisasi, berjemur dan sebagainya, serta kegiatan masa sekarang diadaptasikan ke dalam program dalam bangunan. Program yang diusulkan kemudian menggunakan metode narasi dan pengalaman spasial agar memori narasi yang ingin disampaikan dapat dirasakan pengunjung.  Usulan intervensi yang merupakan sebuah perjalanan rekreasi ini diharapkan dapat mengembalikan rekreasi lokal dan pergerakan warga sekitar.